Karakteristik Mutu Gisuke-ni dan Air Terikat Gisuke-ni Ikan Kembung (Rastrelliger sp.): Quality Characteristics and Bound Water of Mackerel (Rastrelliger sp.) Gisuke-ni - Andarini Diharmi; N Ira Sari; Kenzo Aditya Muhammad Yandhria Putra (Jurnal Pengolahan Hasil Perikanan Indonesia, 2020)
Niboshi is a Japanese traditional of dried of fish products and Gisuke-ni is resulteding from the continued processing of niboshi. This study was aimed to determine the effect of seasoning formula on the sensory and chemical qualitiesy of gisuke-ni, as well as isothermic absorption water and bound water. The design used wais a completely randomized design non factorial complete random design with the different seasoning formulations treatments. The research was carried out consisting of on several stages, namely producing the making of niboshi, followed by the making of gisuke-ni by giving seasoning (sweet, spicy, and salty). Analysis parameters consist ofincluding proximate, organoleptic, sorbpsi isothermic curves of water, and bound water were performed. The results of the analysis of chemical composition (moisture content, protein, ash, fat, and carbohydrate) Niboshi were 21.9, 69.7 (wb), 17.1, 3.2 and 9.8% (ddb), respectively. Gisuke-ni salted seasoning (P1) The levels of moisture, protein, ash, fat, and carbohydrate content on gisuke-ni salted seasoning (P1) were respectively 4.5, 59.8, 16.4, 4.4, and 19.2% (bkdb), respectively, while the . Gisuke-ni sweet seasoning (P2) moisture, protein, ash, fat and carbohydrate content on gisuke-ni sweet seasoning (P_2) were respectively 6.1, 68.3, 13.1, 6.4, and 12.1% (db), respectively. In addition, Spicy Gisuke-ni (P3) contained the moisture content, protein, ash, fat and carbohydrate levels were respectively 8.5, 77.5, 13.3, 6, and 3.0% (db), respectively. The spicy Gisuke-ni spice (P3) The content of primary, sekunder and tersier bound water capacity were 3.51% at aw 0.26, 4.0% at aw 0.79 and 30% at aw 1.0, respectively.